Genes functioned in kleptoplastids of Dinophysis are derived from haptophytes rather than from cryptophytes - Yuki Hongo (Nature Portfolio, 2019)
Abstract Toxic dinoflagellates belonging to the genus Dinophysis acquire plastids indirectly from cryptophytes through the consumption of the ciliate Mesodinium rubrum. Dinophysis acuminata harbours three genes encoding plastid-related proteins, which are thought to have originated from fucoxanthin dinoflagellates, haptophytes and cryptophytes via lateral gene transfer (LGT). Here, we investigate the origin of these plastid proteins via RNA sequencing of species related to D. fortii. We identified 58 gene products involved in porphyrin, chlorophyll, isoprenoid and carotenoid biosyntheses as well as in photosynthesis. Phylogenetic analysis revealed that the genes associated with chlorophyll and carotenoid biosyntheses and photosynthesis originated from fucoxanthin dinoflagellates, haptophytes, chlorarachniophytes, cyanobacteria and cryptophytes. Furthermore, nine genes were laterally transferred from fucoxanthin dinoflagellates, whose plastids were derived from haptophytes. Notably, transcription levels of different plastid protein isoforms varied significantly. Based on these findings, we put forth a novel hypothesis regarding the evolution of Dinophysis plastids that ancestral Dinophysis species acquired plastids from haptophytes or fucoxanthin dinoflagellates, whereas LGT from cryptophytes occurred more recently. Therefore, the evolutionary convergence of genes following LGT may be unlikely in most cases.